About the biology of Steraspis infuscata Thery and data on additional species of Steraspis collected in Benin (Coleoptera, Buprestidae) - Vayssières, Jean-François; Bellamy, C.L. (2012)
Four species of Steraspis Dejean, 1883, have been collected in the centre and the north of Benin in West Africa: Steraspis fastuosa Gerstaecker, 1871, Steraspis infuscata Théry, 1908, Steraspis laetitia Curletti, 2011, and Steraspis modesta Kerremans, 1895. One of the goals of these field observations was to increase the knowledge of the biology of these common but localized species. In May 2011, an adult of S. infuscata was discovered inside the taproot of a Combretum collinum Fresen. (Combretaceae) sapling. This well-developed adult was found seven centimeters below the soil surface and ready to emerge. Prior to pupation, the mature larva had cut along the bottom of the taproot, thus facilitating the emergence of the adult.